The duration of estrogen treatment before progesterone application does not affect neonatal and perinatal outcomes in frozen embryo transfer cycles - Zhang, Junwei; Du, Mingze; Wang, Zhongkai; Wu, Sheling; Guan, Yichun; Sun, Lijun (Frontiers in Endocrinology, 2023)
Objective To explore whether the duration of estrogen treatment before progesterone application affects neonatal and perinatal outcomes in artificial frozen embryo transfer (FET) cycles. Methods This was a retrospective cohort study. Patients who underwent FET via artificial cycles and delivered a singleton live birth between January 2015 and August 2019 were included in the analysis. According to the duration of estrogen treatment before progesterone application, we divided the cycles into four groups: ①≤12 days, ②13-15 days, ③16-19 days, and ④≥20 days. The ‘≤12 days group’ was considered the reference group. The main outcome measures were preterm birth (PTB), small-for-gestational age (SGA), low birth weight (LBW), macrosomia, large-for-gestational age (LGA), gestational diabetes mellitus (GDM), gestational hypertension, premature rupture and placenta previa. Results Overall, 2010 FET cycles with singleton live births were included for analysis. Cycles were allocated to four groups according to the duration of estrogen treatment before progesterone application: ①≤12 days (n=372), ②13-15 days (n=745), ③16-19 days (n=654), ④≥20 days (n=239). The neonatal outcomes, including PTB, SGA, LBW, macrosomia and LGA, were comparable among the groups (P=0.328, P=0.390, P=0.551, P=0.565, P=0.358). The rates of gestational hypertension, premature rupture and placenta previa (P=0.676, P=0.662, P=0.211) were similar among the groups. The rates of GDM among the four groups were 4.0% (15/372), 6.7% (50/745), 6.4% (42/654), and 11.3% (27/239), with statistical significance (P=0.006). After multiple logistic regression analysis, the duration of estrogen treatment did not affect the rate of GDM or other outcomes. Conclusion The estrogen treatment duration before progesterone application does not affect neonatal and perinatal outcomes in single frozen blastocyst transfer cycles.